Effective methods of rational water resource use in the agrarian sector of Kazakhstan - Yerzhan Amirbekuly; Adaskhan Daribayeva; Aigul Toxanova; Darima Zhenskhan; Nurzhamal Kurmankulova (Наукові горизонти)
The study aimed to determine effective methods of rational water resources use in the agricultural sector of Kazakhstan. The impact of modern irrigation technologies, such as drip and sprinkler irrigation, as well as automated monitoring systems on crop productivity, soil condition and adaptability of farms to climate change was analysed. Drip irrigation was noted to reduce water losses by up to 40%, while sprinkler systems provided uniform coverage of large areas, optimising water resources. Automated monitoring systems using soil moisture sensors and weather forecasting reduced water consumption by 25-50% and increased crop yields by 15-30%. The study also determined that introducing such systems improved soil quality, reducing depletion and ensuring long-term productivity. An analysis of the experience of farms in Kazakhstan, Israel, Spain and China confirmed the economic feasibility of such approaches by reducing operating costs as well as dependence on external financing and increasing resilience to climatic stresses. In particular, automation of water supplies reduced water, energy and system maintenance costs, which ensured long-term farm stability. The practical value of the work was the formation of scientifically based recommendations for the introduction of innovative irrigation technologies to improve the efficiency of the agricultural sector of Kazakhstan, reduce the impact of climate change and ensure sustainable development